2021
DOI: 10.1016/j.clinph.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Phase-amplitude coupling of ripple activities during seizure evolution with theta phase

Abstract: High-frequency activities (HFAs) and phase-amplitude coupling (PAC) are gaining attention as key neurophysiological biomarkers for studying human epilepsy. We aimed to clarify and visualize how HFAs are modulated by the phase of low-frequency bands during seizures. MethodsWe used intracranial electrodes to record seizures of symptomatic focal epilepsy (15 seizures in seven patients). Ripples (80-250 Hz), as representative of HFAs, were evaluated along with PAC. The synchronization index (SI), representing PAC,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
(26 reference statements)
3
17
0
Order By: Relevance
“…Epilepsy studies reported a positive correlation between coupling values and high-frequency amplitude (Hashimoto et al, 2021a;Weiss et al, 2016). We showed the continuous positive correlation between…”
Section: Profiles Of Motor-and Sensory-related Pacsupporting
confidence: 67%
See 3 more Smart Citations
“…Epilepsy studies reported a positive correlation between coupling values and high-frequency amplitude (Hashimoto et al, 2021a;Weiss et al, 2016). We showed the continuous positive correlation between…”
Section: Profiles Of Motor-and Sensory-related Pacsupporting
confidence: 67%
“…EEG studies suggest that q oscillations are related to both sensory and motor behaviors (Tomassini et al, 2017) and a general property of brain activity (Ramayya et al, 2020). In the epileptic brain, the hippocampal q rhythm was increased (Kitchigina and Butuzova, 2009) and seizure-related HFA was coupled with q band (Hashimoto et al, 2020b(Hashimoto et al, , 2021a. The q oscillations are involved in both sensory and motor neural processing, and both physiological and pathological neural processing, and in this study, we provide a new insight into the sensory-related q-HG coupling.…”
Section: Profiles Of Motor-and Sensory-related Pacmentioning
confidence: 99%
See 2 more Smart Citations
“…PAC analysis measures the degree of synchronization between the phases with low-frequency oscillation and high-frequency amplitude 18 . Ictal HFA amplitudes coupled with δ 19 , 20 , θ 21 , 22 , and α 21 phases, and β-HFA coupling are reported as useful markers for seizure detection 23 . Moreover, coupling θ waves with HFOs has been reported to well discriminate normal brain regions from the seizure onset zone (SOZ) 24 .…”
Section: Introductionmentioning
confidence: 99%